2012
DOI: 10.2478/s11696-011-0129-8
|View full text |Cite
|
Sign up to set email alerts
|

Doping level of Mn in high temperature grown Zn1−x MnxO studied through electronic charge distribution, magnetization, and local structure

Abstract: Mn inclusion in the oxide based diluted magnetic semiconductor Zn1−x MnxO (x = 0.04, 0.06, 0.08, and 0.10) grown by standard high temperature solid state reaction technique has been studied. The local and average structure of Zn1−x MnxO was characterized by the super resolution technique maximum entropy method and pair distribution function analysis using the X-ray powder data. Magnetic studies on this material using a Vibrating Sample Magnetometer were also carried out to ascertain the doping level in Zn1−x M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Substitution of Mn for Zn 2+ requires local expansion or contraction of the lattice to accommodate the manganese ion due to ionic radii differences. Since Mn can exist as Mn 2+ , Mn 3+ and Mn 4+ (respective ionic radii are 0.83Å, 0.65Å and 0.53Å), one cannot be certain of the actual distribution of Mn in the lattice [22], [23]. If Mn 2+ ion of greater ionic radius substitutes Zn 2+ (0.74 Å), the peaks will shift towards the lower angles because of increase in d-spacing due to substitution of lattice site by ion of higher radius.…”
Section: Solubility Of Mn In Zno Nanocrystallites Using Wet Chemical mentioning
confidence: 99%
“…Substitution of Mn for Zn 2+ requires local expansion or contraction of the lattice to accommodate the manganese ion due to ionic radii differences. Since Mn can exist as Mn 2+ , Mn 3+ and Mn 4+ (respective ionic radii are 0.83Å, 0.65Å and 0.53Å), one cannot be certain of the actual distribution of Mn in the lattice [22], [23]. If Mn 2+ ion of greater ionic radius substitutes Zn 2+ (0.74 Å), the peaks will shift towards the lower angles because of increase in d-spacing due to substitution of lattice site by ion of higher radius.…”
Section: Solubility Of Mn In Zno Nanocrystallites Using Wet Chemical mentioning
confidence: 99%
“…The MEM electron densities compiled from the experimental information are used for the visualization of the 3D electron density using the software VESTA (Koichi Momma and Fujio Izumi, Japan) [40]. The MEM electron density studies for various systems such as Na, V, Si, GaAs, Ge, etc., have already been reported elsewhere [41][42][43][44][45].…”
Section: Powder Xrd Data and Charge Densitymentioning
confidence: 70%
“…If the valence state is Mn 3+ or Mn 4+ then, there is a possibility of Mn-Mn distances reduction. With a regular pattern in increment of the Mn concentration, there should be a uniform shift in the parameters as the Mn concentration increases [7]. However, variations in the trend were observed showing that the difference is not uniform with respect to the Mn concentration.…”
Section: Solubility Of Mn In Zno Crystallites Synthesized Using Solidmentioning
confidence: 91%
“…Research has shown that, substitution of a fraction of the original atoms of the lattice of ZnO host by one of the transition metal (TM) ions especially, Mn, Co, Fe, and Cr and Ni, in appropriate concentrations in the host material, could introduce ferromagnetic properties while its semiconducting property is retained making the material a dilute magnetic semiconductor (DMS). By combining both semiconducting and ferromagnetic properties, DMS can lead to spintronic devices that use both spin and charge of electrons [7,8]. Mn has the advantage of being used as a dopant because of its high magnetic moment and the relatively small ionic radii difference between Mn 2+ and Zn 2+ which facilitates its incorporation into the ISSN: 2581-5164 Available online at Journals.aijr.in…”
Section: Introductionmentioning
confidence: 99%